2016
DOI: 10.1002/hed.24454
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of midtreatment FDG‐PET in oropharyngeal cancer

Abstract: Metabolic response during chemoradiation is associated with survival in locally advanced oropharyngeal cancer and may aid with risk-adapting treatment. © 2016 Wiley Periodicals, Inc. Head Neck 38: First-1478, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
4
30
0
Order By: Relevance
“…Several studies have demonstrated the ability of MTV and TLG to predict treatment outcomes in OPSCC. [16][17][18][19][20]22,[24][25][26][27][28][29] However, literature testing of its prognostic value specifically in patients with HPV-related OPSCC patients and a ≤10 packyear smoking history is scarce. Given the need for and lack of effective prognostic biomarkers for LRF in HPV-related OPSCC, we sought to investigate the prognostic value of MTV and TLG in this patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the ability of MTV and TLG to predict treatment outcomes in OPSCC. [16][17][18][19][20]22,[24][25][26][27][28][29] However, literature testing of its prognostic value specifically in patients with HPV-related OPSCC patients and a ≤10 packyear smoking history is scarce. Given the need for and lack of effective prognostic biomarkers for LRF in HPV-related OPSCC, we sought to investigate the prognostic value of MTV and TLG in this patient group.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging with CT and 18 F-FDG PET is often used in staging, radiation treatment planning, and response evaluation for patients with OPSCC (6,7). Numerous studies have investigated imaging characteristics associated with treatment outcomes, with limited success (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Most previous studies, however, analyzed baseline imaging before the initiation of therapy.…”
mentioning
confidence: 99%
“…TLG was a significant prognostic factor for OS in patients with tonsil cancer [ 18 ]. In a study of 74 oropharyngeal cancer patients who received CCRT, both pre-treatment and midtreatment MTV were associated with OS and PFS [ 19 ]. In a meta-analysis of more than 1,100 head and neck cancer patients, both MTV and TLG of pretreatment PET/CT were prognostic factors for OS [ 17 ].…”
Section: Discussionmentioning
confidence: 99%